Establishment of driteria, preservation and utilization of lina in the production of puto sulot - Villanueva, Katrina L.
Puto sulot is a fried flour-coconut based product from Barili, Cebu which traditionally uses lina (freshly-gatheres tuba or coconut sap without baluk) as starter.